The Study of the Level of Knowledge, Attitude, Practices (KAP) as well as the Effects of School Environment on the Nutritional Status of Children (7-12) Coming from Affluent Families in the Dhaka City in Bangladesh - Saha, Sanjoy; Zahid, Md Khurshidul; Rasheed, Sabrina (Bangladesh Journal of Nutrition, 2013)
The study find-out the level of knowledge, attitude and practices and effects of school environment on the nutritional status of children (7-12 yrs) coming from affluent society in Dhaka city in Bangladesh. Majority (68.31%) of the students have basic Nutritional Knowledge but only 70.20 % students have correct basic Nutritional Knowledge. Each school gives basic nutrition education to their students along with the general courses, so that the students as well as their parents adopt healthy eating practices. All schools have classroom teaching programme related to Food and Nutrition. On average students spend 4.8 hours per day at school. Though all schools have indoor sports facilities but students are mostly involved in sedentary activities. Majority (86.5%) of the students participates in indoor sports & extracurricular activities at school as well as almost half (47.91%) of the students take part in outdoor sports. One fifth (18.75%) of students spend more than one hour in extracurricular activities. From this study it is found that there is a significant negative relationship between duration of physical activity (sports and extracurricular activities) at school and over-nutrition (obesity & overweight). In case of students parents, most (59.37%) of the fathers are businessman and most (67.7%) of the mothers are housewife. About 59 % of students get their pocket money from their mother. About two-third (65.6%) of students take foods from the shops for their school meal and only one third (34.4%) of the students bring foods from home for their school meals. Students spend on an average 24 taka at school to buy foods. Each school have indoor food facilities. Most foods available in the shops inside the schools are fast foods which are mainly rich in calories. Most (72.9%) students consume fast foods and fried foods in school hours. They mostly prefer fast foods and soft drinks who buy foods at school. Intake of fruits, milk and milk product is low. If he or she get extra pocket money then they prefers to buy firstly ice-cream and then chocolate, soft drinks and fruit juices which are mainly energy rich foods. Most (78.1%) students consume fast foods while they are at school but while they are away from school they preferred to take dairy products (96.7%) as well as fruits and vegetables (93.7%). Most of the students (92.70%) take fast foods 1-3 times per week while three fourth of the students (75%) students drink soft drinks 1-3 times per week. Majority of students prefer to have fast foods (68.75%) and soft drinks (58.33%) at afternoon. There is no significant relationship between fast food intake at school and overweight development. High percentage of overweight among the studied subjects possibly due to total intake both at home and outside. From the study we can say that if both the students and parents are given sufficient nutritional knowledge then there is a fair chance to develop a healthy environment in each school which will lead them to choose and eat healthy foods to make their diet balanced. We need immediate measures to control malnutrition problems of children coming from affluent societies in Dhaka city. If proper steps are taken quickly then we can hope a healthy nation with healthy children. DOI: http://dx.doi.org/10.3329/bjnut.v24i0.14035 Bangladesh J. Nutr. Vol. 24-25 Dec 2011-2012 pp.31-48